TRANSFORMATIONAL LEADERSHIP STRATEGIES IN ISLAMIC EDUCATIONAL INSTITUTIONS - Ahmad Aji Pangestu; M. Ridho Muttaqin; Eri Dwi Cahyanti (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
Transformational leadership is a leadership approach capable of promoting comprehensive change within organizations, including in Islamic educational institutions. Transformational leaders act not only as managers but also as inspirers, motivators, and moral role models who shape organizational culture based on Islamic values. This study aims to analyze transformational leadership strategies applicable in Islamic educational settings through a qualitative approach using library research methods. The findings indicate that strategies such as vision inspiration, moral exemplification, intellectual stimulation, individual consideration, and collective participation are essential in building adaptive, spiritual, and progressive educational institutions. This research is expected to contribute theoretically to the development of an integrative leadership model combining Islamic values with modern management practices.